Global Burden of Esophageal Cancer and Its Risk Factors: A Systematic Analysis of the Global Burden of Disease Study 2019 - Irena Ilic; Ivana Zivanovic Macuzic; Ana Ravic-Nikolic; Milena Ilic; Vesna Milicic (Life)
Background: Esophageal cancer is a major public health issue, yet risk factors for its occurrence are still insufficiently known. This study aimed to estimate the global burden of esophageal cancer and its risk factors. Methods: This ecological study presented the incidence, mortality, and Disability-Adjusted Life Years (DALYs) of esophageal cancer in the world. This study collected the Global Burden of Disease study data from 1990 to 2019. Trends in esophageal cancer burden were assessed using the joinpoint regression analysis and calculating the average annual percent change (AAPC). Results: Globally, in 2019, in both sexes and all ages, the ASR for the incidence of esophageal cancer was 6.5 per 100,000 and for mortality, 6.1 per 100,000. The global proportion of DALYs for esophageal cancer attributable to selected behavioral, metabolic, and dietary risk factors was similar in males and females: chewing tobacco (3.8% vs. 5.1%), diet low in fruits (10.1% vs. 12.6%), diet low in vegetables (3.3% vs. 4.6%), and high body mass index (18.8% vs. 19.3%). However, the proportion of DALYs for esophageal cancer attributable to smoking and alcohol use was 4–5 times higher in males than in females (50.1% vs. 11.3%, and 29.6% vs. 5.1%, respectively). From 1990 to 2019, a significant decrease in global trends in rates of DALYs for esophageal cancer attributable to smoking (AAPC = −1.6%), chewing tobacco (AAPC = −0.5%), alcohol use (AAPC = −1.0%), a diet low in fruits (AAPC = −3.1%), and a diet low in vegetables (AAPC = −3.6%) was observed, while a significant increase in trends was observed in DALYs rates for esophageal cancer attributable to a high body mass index (AAPC = +0.4%). Conclusions: More epidemiological research is needed to elucidate the relationship between esophageal cancer and certain risk factors and guide prevention efforts.